Immune homeostasis, dysbiosis and therapeutic modulation of the gut microbiota - Peterson, C T (Clin Exp Immunol, 2015)
The distal gut harbours ∼10(13) bacteria, representing the most densely populated ecosystem known. The functional diversity expressed by these communities is enormous and relatively unexplored. The past decade of research has unveiled the profound influence that the resident microbial populations bestow to host immunity and metabolism. The evolution of these communities from birth generates a highly adapted and highly personalized microbiota that is stable in healthy individuals. Immune homeostasis is achieved and maintained due in part to the extensive interplay between the gut microbiota and host mucosal immune system. Imbalances of gut microbiota may lead to a number of pathologies such as obesity, type I and type II diabetes, inflammatory bowel disease (IBD), colorectal cancer (CRC) and inflammaging/immunosenscence in the elderly. In-depth understanding of the underlying mechanisms that control homeostasis and dysbiosis of the gut microbiota represents an important step in our ability to reliably modulate the gut microbiota with positive clinical outcomes. The potential of microbiome-based therapeutics to treat epidemic human disease is of great interest. New therapeutic paradigms, including second-generation personalized probiotics, prebiotics, narrow spectrum antibiotic treatment and faecal microbiome transplantation, may provide safer and natural alternatives to traditional clinical interventions for chronic diseases. This review discusses host–microbiota homeostasis, consequences of its perturbation and the associated challenges in therapeutic developments that lie ahead.